Gamification in a Blended Learning Environment: The Mojo of ClassDojo - Chuah, Kee Man; Fitri Suraya, Mohamad (Penerbit Universiti Pendidikan Sultan Idris, 2021)
Although ClassDojo can be directly used, this chapter reports how it was applied to a course through gamified modules. The modules were designed using the core drives in Octalysis model. There are 8 core drives in the model, but the study only applied four core drives: Epic meaning and calling, Development and accomplishment; unpredictability and curiosity; and loss and avoidance. Details on these core drives can be obtained via Chou (2015) or https://yukaichou.com. The modules cover 7 units in a course which focus on computational linguistics, and each module was labelled as a stage in the gamified world. As they completed the challenges set for each stage, their progress was monitored via ClassDojo instead of using conventional ways such as Excel Sheets or whiteboard. Any action or behaviour that is commendable was also given points. ClassDojo makes learning “visible” as students can monitor their learning, which indirectly promotes self-regulated learning.